Knowledge and Attitude toward Antibiotic Use and Identification of Financially Feasible Options to Curb the Spread of Antibiotics in Environment - Mayank Krishna; Nilesh Makwana; Ganesh S. Kakde; Sapna Puri; Arun S. Kharat (Canadian Journal of Infectious Diseases and Medical Microbiology)
A survey on antibiotic literacy in terms of the use and abuse of antibiotics to track and understand antibiotic consumption is crucial to optimize the use of antibiotics and minimizing antimicrobial resistance (AMR). Purposive random sampling, using the snow-ball questionnaire technique, was adopted to ensure that the respondents distributed across India, coming from rural and urban settings, were adolescents as well as adults and had completed at least the higher secondary school level of education. Respondents were divided into five subcategories. The questionnaire was distributed between April 2021 and July 2021, during the second COVID-19 wave in India. The survey questionnaire included 34 questions, comprising multiple-choice and 5-point Likert scale-type questions. This study composed of 972 respondents. Most respondents considered antibiotics safe and frequently failed to discriminate between the symptoms of bacterial and viral infections, most often leading to self-prescription. About 34% of the rural participants and 50% of the urban participants considered antibiotic resistance a serious health concern. Antibiotic prescriptions by the medical or paramedical practitioner were largely empirical. At least 95% of participants acknowledged having heard about antibiotics; nearly 20% of antibiotic consumption came from nonprescription users, while 30% had not completed their antibiotic therapy for a variety of reasons. Sixty-two percent consumed antibiotics to treat cold and flu symptoms. Results from the survey suggest the presence of a crucial gap between the respondents’ perception of antibiotics and levels of information regarding antibiotic use and misuse. The present study may serve as a benchmark that strongly recommends a financially feasible policy, which includes educating society regarding the spread of AMR and its severe consequences by incorporating AMR into the curriculum at the levels of senior secondary school and higher education.